Virtual coaching for rehabilitation: the participatory design experience of the vCare project - Seregni, Agnese; Tricomi, Enrica; Tropea, Peppino; Del Pino, Rocio; Gómez-Esteban, Juan Carlos; Gabilondo, Inigo; Díez-Cirarda, María; Schlieter, Hannes; Gand, Kai; Corbo, Massimo (Frontiers in Public Health, 2021)
End-user involvement constitutes an essential goal during the development of innovative solution, not only for the evaluation, but also in codesign, following a user-centered strategy. Indeed, it is a great asset of research to base the work in a user-centered approach, because it allows to build a platform that will respond to the real needs of users. The aims of this work are to present the methodology adopted to involve end-users (i.e., neurological patients, healthy elderly, and health professionals) in the evaluation of a novel virtual coaching system based on the personalized clinical pathways and to present the results obtained from these preliminary activities. Specific activities involving end-users were planned along the development phases and are referred to as participatory design. The user experience of participatory design is constituted by the two different phases: the “end-user's perspective” phase where the user involvement in experiential activities is from an observational point of view, whereas the “field study” phase is the direct participation in these activities. Evaluation tools (i.e., scales, questionnaires, and interviews) were planned to assess different aspects of the system. Thirty patients [14 with poststroke condition and 16 with Parkinson's disease (PD)], 13 healthy elderly, and six health professionals were enrolled from two clinical centers during the two phases of participatory design. Results from “end-user's perspective” phase showed globally a positive preliminary perception of the service. Overall, a positive evaluation (i.e., UEQ median score > 1) was obtained for each domain of the scale in both groups of patients and healthy subjects. The evaluation of the vCare system during the “field study” phase was assessed as excellent (>80 points) from the point of view of both patients and health professionals. According to the majority of patients, the rehabilitation service through the solution was reported to be interesting, engaging, entertaining, challenging and useful for improving impaired motor functions, and making patients aware of their cognitive abilities. Once refined and fine-tuned in the aspects highlighted in the this work, the system will be clinically tested at user's home to measure the real impact of the rehabilitative coaching services.
Gesehen am 27.01.2022